91.5k views
2 votes
Select the correct product.

(2x + 9)(x + 1)

2x^2 + 11x + 9
3x^2 + 11x + 9
2x^2 - 7x + 9
2x^2 + 11x + 10

User Minioim
by
7.3k points

1 Answer

3 votes
Use the FOIL method.
F = First
O = Outer
I = Inner
L = Last

Step 1: Multiply the First terms of each binomial

2x * 2 = 2x^2

Step 2: Multiply the Outer terms

2x * 1 = 2x

Step 3: Multiply the Inner terms

9 * x = 9x

Step 4: Multiply the Last terms of each expression

9 * 1 = 9

Step 5: List the results of FOIL in order

2x^2 + 2x + 9x + 9

Step 6: Combine like terms to get your final answer

2x^2 + 11x + 9
User Satran
by
7.4k points